2004
DOI: 10.1002/humu.9243
|View full text |Cite
|
Sign up to set email alerts
|

Loss-of-function mutations in cathepsin C in two families with Papillon-Lefèvre syndrome are associated with deficiency of serine proteinases in PMNs

Abstract: Papillon-Lefèvre syndrome (PLS) is a rare autosomal recessive disease that involves severe periodontitis and hyperkeratosis of the hand palms and foot soles. Recently it was found that PLS patients carry loss-of-function mutations in the gene encoding cathepsin C (CTSC). In the present study we have analyzed the CTSC gene in two unrelated families with PLS. In the first non-consanguineous family, mutation analysis revealed the previously reported c.815G>C/p.R272P mutation. The second consanguineous family disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
84
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 21 publications
2
84
0
3
Order By: Relevance
“…The patients showed no cathepsin C activity, and the mother had reduced (50%) levels. We confirmed that the patients were deficient for elastase, cathepsin G, and proteinase 3 activity (16).…”
Section: Methodssupporting
confidence: 72%
See 2 more Smart Citations
“…The patients showed no cathepsin C activity, and the mother had reduced (50%) levels. We confirmed that the patients were deficient for elastase, cathepsin G, and proteinase 3 activity (16).…”
Section: Methodssupporting
confidence: 72%
“…Genomic DNA was isolated from the blood samples by using the Puregene kit (Gentra Systems, Inc., Michigan) according to the manufacturer's protocol. Sequencing was performed as described previously (16). In family C, a previously reported mutation, c.815GϾC/p.R272P, was found (72).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This enzyme is required for removal of two N-terminal amino acids that block the active site of neutrophil serine proteases (62). Failure to remove these two N-terminal amino acids results in the inability to generate active enzyme and complete degradation of the serine proteases before mature neutrophils are formed (11,63,64). These patients are therefore completely devoid of all neutrophil serine proteases, including elastase, and hence incapable of generating NETs (11), except by saliva (18).…”
Section: Are Nets Important For Immune Defense?mentioning
confidence: 99%
“…First, activated lymphocytes derived from humans with congenital deficiency of CatC (PapillonLefevre syndrome) contain active GrB and kill target cells with similar efficiency to healthy controls (10). Papillon-Lefevre syndrome patients present principally with manifestations of neutrophil dysfunction, such as severe gingivitis, because the neutrophil serine proteases cathepsin G and elastase depend completely on CatC for processing (10,11). Secondly, lymphocytes from CatC Ϫ/Ϫ mice possess active GrB and kill target cells almost as efficiently as wild-type mice (12).…”
mentioning
confidence: 99%